Tinjauan Metode Mengajar dan Hasil Belajar Siswa Sekolah Menengah Atas dalam Mata Pelajaran Penjasorkes - Deffri Anggara; Supriyanto Supriyanto (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aimed to analyze teaching methods and learning outcomes at SMA Negeri 3 Bengkulu Selatan. The data collection technique is through a questionnaire and is included in the type of descriptive research. The results showed that the classification of male learning outcomes who got perfect scores was one person (2.27%), who got good grades five people (11.36%), who got average scores of 11 people (25.00%), who got 20 people (45.45%) less score, while seven people (15.91%). At the same time, the girls got excellent marks ten people (40.00%), who got good marks five people (20.00%), who got average scores five people (20.00%), who got fewer marks two people (8,00%), while those who get a score of less than once are three people (12.00%). The conclusion is that the teaching methods and learning outcomes of high school students in physical education subjects at SMA Negeri 3 Bengkulu Selatan are in a suitable category. Keywords: Learning Outcomes, Teaching Methods